VEHICLE AND VEHICLE CONTROL METHOD - SANADA TAKERU; AKIBA MASAYA (2023)
To enable use of large regenerative braking force to be enhanced while curbing early execution of antilock brake control.SOLUTION: A vehicle comprises: a regenerative braking device; a friction braking device; and an electronic control unit. The regenerative braking device is installed on regenerative braking wheels which are either front wheels or rear wheels. The friction braking device is adapted to be able to individually control friction braking force to be applied to the front and rear wheels. When detecting a slip sate where a wheel speed of a wheel subject to regenerative braking is lower than a slip determination threshold positioned between a body speed of the vehicle and an execution threshold of antilock brake control, the electronic control unit executes regenerative braking treatment controlling the regenerative braking device so as to generate regenerative braking force reducing a deviation of the wheel speed of the wheel subject to the regenerative braking from the slip determination threshold.SELECTED DRAWING: Figure 5 【課題】アンチロックブレーキ制御の早期作動を抑制しつつ大きな回生制動力の利用を促進できるようにする。【解決手段】車両は、回生制動装置と、摩擦制動装置と、電子制御ユニットと、を備える。回生制動装置は、前輪及び後輪の何れか一方である回生制動輪に対して設けられている。摩擦制動装置は、前輪及び後輪に付与される摩擦制動力を個別に制御可能に構成されている。電子制御ユニットは、回生制動を行っている回生制動輪の車輪速度が車両の車体速度とアンチロックブレーキ制御の作動閾値との間に位置するスリップ判定閾値を下回るスリップ状態を検知した場合、スリップ判定閾値に対する回生制動輪の車輪速度の偏差を小さくする回生制動力を生じさせるように回生制動装置を制御する回生制御処理を実行する。【選択図】図５